The relevance of probiotics in therapy - Grzeszczak, Konrad; Strońska, Aleksandra; Rogulska, Karolina (Journal of Education, Health and Sport, 2021)
Probiotics are live microorganisms that have a positive effect on human health, in particular on the intestinal microbiota. It turned out that they not only perform an important role in the intestinal microbiota, but also affect the functioning of the immune system, reduce the incidence of allergies or significantly reduce the risk of certain types of cancer. Thanks to the proven benefits of probiotics, scientists are now looking into their use in the treatment of many diseases. The examples are Helicobacter pylori infection, Irritable Bowel Syndrome and Respiratory Tract Infection, where the significant benefits of probiotics have been proved. Until recently it was thought that they were only useful in gastrointestinal diseases, but the use of probiotics in Respiratory Tract Infection shows that probiotics can also be used to treat other diseases. Further research into the impact of probiotics on therapy is highly desirable in order to match the effects of specific strains to specific diseases.